Relationships between customer satisfaction, service quality, Feng Shui and corporate image of a Malaysian company - Wong, Shin Yee (2015)
Corporate image is an influencing factor for organizational commitment among customers. Nevertheless, it remains uncertain as to the extent of influence customer satisfaction and service quality possesses towards shaping the corporate image of property developers. This research mainly places focus on the influences of customer satisfaction, service quality offered by property developers and the buyers’ perception on Feng Shui culture and how this in turn affects their purchasing decision. The aforementioned variables studied subsequently forms the positive corporate image. Impression management theory and a conceptual model based on Nguyen’s and LeBlanc’s (1998) research is applied to this study that specifically analyses the perceptions of customers towards developers’ corporate image in terms of their satisfaction and service quality of the property. This research also looks into a typically non-traditional field of Feng Shui influences examining the perception of customers towards the property’s Feng Shui on developers’ corporate image. The quantitative method survey was applied on a sample of 93 respondents from selected property units using purposive sampling technique. The survey uses both descriptive and analytical methods. Correlation and multiple regression analysis were used to test the relationships between independent and dependant variables. The pilot test exhibited that the instrument has good construct validity. Moving forward, this study will lead to better insight of the complex relationships between corporate image, customer satisfaction, service quality and Feng Shui culture. The key findings suggest service quality as a vital factor in the context of the real estate industry. Moreover, it is equally important to note that that Feng Shui indeed plays a supporting role in creating a positive corporate image. Recommendations are also made available for future studies in this field.